Risk factors of unfavourable TB treatment outcomes in Hulu Langat, Selangor - Kaur, Kirandeep Kulwant; Md Said, Salmiah; Syed Ismail, Sharifah Norkhadijah; Lim, Poh Ying (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Over the last decade, tuberculosis (TB) has remained the main cause of death from communicable diseases in Malaysia. This study was aimed to determine the risk factors of unfavourable treatment outcomes (UTO) among new TB cases in Hulu Langat. Methods: A cohort study was prospectively conducted among the new TB cases registered in the government health clinics of Hulu Langat district. The event was defined as any one of the UTO (default, transferred out, treatment failure and death) whichever came first. This data was analysed using SPSS version 25.0. Survival pattern was assessed by Kaplan-Meier plots and Log rank test. Hazard ratios of unfavourable TB treatment outcomes among the new TB cases at 95% confidence interval and level of significance set at 0.05 were calculated using Cox proportional hazard model. Results: Of the 321 patients analysed, 80.4% (n=258) had favourable treatment outcomes and 19.6% (n=63) had UTO with 10.9% (n=35) transferred out, 6.9% (n=22) defaulted and 1.9% (n=6) died. There was no treatment failure. The mean survival time was 5.2 (SD=0.09) months. The risk factors of hazard probability of UTO were male, ethnicity type Others, positive human immunodeficiency virus (HIV) status and not done sputum at 2 months of treatment. Conclusion: Transferred out and default formed the bulk of the UTO in Hulu Langat. New interventions to improve the existing TB prevention and control program should be planned in the first three months of treatment.